Tracheoplasty... Reconstructing a new airway - Waugh, Patricia (Operating Room Nurses Association of Canada Journal, 1987)
As a member of the operating room team, the O.R. nurse is often a witness to many skillful and unique surgical procedures. The Hospital for Sick Children in Toronto has seen its share of these "surgical miracles." The following is a brief description of a particularly unique procedure that began several years ago.